2014
DOI: 10.1371/journal.pone.0088728
|View full text |Cite|
|
Sign up to set email alerts
|

Prognosis of 18 H7N9 Avian Influenza Patients in Shanghai

Abstract: PurposeTo provide prognosis of an 18 patient cohort who were confirmed to have H7N9 lung infection in Shanghai.MethodsPatients' history, clinical manifestation, laboratory test, treatment strategy and mortality were followed and recorded for data analysis.ResultsA total of 18 patients had been admitted into Shanghai Public Health Clinical Center from April 8th to July 29, 2013. 22.2% of the patients were found to have live poultry contact history and 80% were aged male patients with multiple co-morbidities inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 28 publications
0
21
1
1
Order By: Relevance
“…Epidemiological studies have shown that H7N9 virus infections have affected mainly middle-aged or older individuals (Figure 2C; i.e., the median age at infection is 63 years) 1929 . Interestingly, two-thirds of the infected individuals have been male 19, 20, 2224, 2729 (Figure 2C).…”
Section: Epidemiology Of Human H7n9 Virus Infectionsmentioning
confidence: 99%
See 3 more Smart Citations
“…Epidemiological studies have shown that H7N9 virus infections have affected mainly middle-aged or older individuals (Figure 2C; i.e., the median age at infection is 63 years) 1929 . Interestingly, two-thirds of the infected individuals have been male 19, 20, 2224, 2729 (Figure 2C).…”
Section: Epidemiology Of Human H7n9 Virus Infectionsmentioning
confidence: 99%
“…Interestingly, two-thirds of the infected individuals have been male 19, 20, 2224, 2729 (Figure 2C). The high number of cases among elderly men may reflect socio-economical differences among age groups and genders since elderly men may have frequent work-related or non-job-related contact with poultry.…”
Section: Epidemiology Of Human H7n9 Virus Infectionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Clinical data suggested that H7N9 caused pneumonia with various degrees of severity, acute lung injury, acute respiratory distress syndrome, and even multiple organ failure. Increased concentrations of C reactive protein were found to be closely associated with mortality (Lu et al 2014). According to published reports, the median age of patients who died of H7N9 was significantly higher than that of patients with nonfatal cases.…”
Section: Discussionmentioning
confidence: 99%